Care for diabetes patients using the Staged Diabetes Management protocol: an experience report - doi:10.5020/18061230.2006.p253 - Maria Lúcia Zanetti; Liudmila Miyar Otero; Maria Cristina Foss Freitas; Manoel Antônio dos Santos; Fernanda Pontin de Mattos Guimarães; Carlos Eduardo Barra Couri; Denise Siqueira Peres; Antonio Augusto Ferronato; Karina Dal Sasso; Anelise Siman Barbieri (Universidade de Fortaleza, 2012)
The work in multi professional health team has been acknowledged as important for the diabetic patient education. This study aimed at describing the implementation of a care assistance program using the Staged Diabetes Management (SDM) protocol; also, characterizing the activities performed by the multi professional health team of the Nurse Education Center for Adults and Elderly, from Ribeirão Preto, in the treatment of diabetic patients. The study was developed from April, 2004 to April, 2005 through weakly meetings, combining individual and group activities coordinated by nurses, physicians, nutritionists, psychologists and physical educators. The results showed that the use of the SDM protocol contributed to improve diabetic patient's metabolic control and consequently, drug cover up for diabetes mellitus, arterial hypertension and dislipidemia; also, increased the adherence to the nutrition program, to physical activity and the knowledge about the disease; and yet, reduced the signs and symptoms referred by the patients. This experience, showed the viability of implanting the referred protocol. The authors believe that the disclosure of this type of study might contribute to the guides commended by World Health Organization for the care of diabetic patients, specially the disease's self-managed care.